Prevalence and correlates of back pain or problems among a nationally representative population-based sample of older adults in India in 2017-2018 - Pengpid S. (2023)
This study aimed to determine the prevalence and correlates of self-reported back pain or problem in older adults in India. The cross-sectional sample consisted of 52,393 individuals (≥50 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017-2018. Results indicate that the prevalence of past 2-years back pain or problem was 32.4%, 36.8% among women and 27.1% among men. In adjusted logistic regression analysis, older age, married, food insecurity, experiencing 3-6 types of discrimination, exposure to stressful life events, and major depressive disorder were positively associated with 2-year back pain or problem, while male sex, higher education and underweight were negatively associated with 2-year back pain or problem. In addition, in unadjusted analysis, higher subjective socioeconomic status, overweight and lifetime alcohol use were negatively associated with 2-year back pain or problem. Almost two in five older adults in India reported 2-year back pain or problem. Several risk factors were identified, which can be targeted in public health interventions.